Pentingnya Peran Chief Officer Dalam Penanganan Bongkar Muat Kontainer di Atas Kapal - Handriyan Angga P; B.L Hentri Widodo; Eni Tri Wahyuni; Aan Rubiyanto (Politeknik Bumi Akpelni Semarang, 2025)
The purpose of this paper is to discuss the importance of the chief officer's role in the loading and unloading process on a ship. Loading and unloading containers on a ship must be carried out as well as possible, in relation to the safety of the ship, crew and cargo. Because the stability of the ship also depends on the handling of the cargo that has been arranged, so in this case the chief officer is responsible for everything related to loading and unloading. The chief officer is the head of the deck department, is one of the management levels of the four deck department officers who are directly responsible to the captain and is the second person in charge after the captain. One of the duties of the chief officer is to carry out supervision during loading and unloading activities. In this case, the role of the chief officer is very necessary considering the main tasks he carries out and the need for knowledge to carry out these tasks. The method used by the author in compiling this research is by collecting data through observation, interviews, and literature studies. The discussion obtained data related to the importance of the chief officer's role in the loading and unloading process of containers on the ship. The results of this paper are about the importance of the chief officer's role in handling loading and unloading as a reference and provision for an officer on the ship later. The conclusion of this writing is the importance of the role of the chief officer in the loading and unloading process on the ship. And a chief officer must be able to calculate the GM stability of the ship.